Presidential Decree-Law No. 77 of the Year 2013 On Amending Some Provisions of the Penal Code = قرار رئيس جمهورية مصر العربية بالقانون رقم 77 لسنة 2013 فى شأن تعديل بعض أحكام قانون العقوبات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.